Manajemen Program Pembelajaran Bahasa Arab dalam Meningkatkan Kompetensi Bahasa Santri di Pondok Pesantren - Muhammad Ramadhan; Nuril Mufidah (Al-Kindi, 2026)
Arabic language learning plays a very important role in Islamic educational institutions, especially in Islamic boarding schools (pesantren). Arabic functions not only as a means of communication but also as a medium for understanding the primary sources of Islamic teachings such as the Qur'an and Hadith. Therefore, effective management of Arabic language learning programs is required in order to achieve learning objectives optimally. This study aims to analyze the management of Arabic language learning programs in improving the language competence of santri (Islamic boarding school students) in pesantren. This research uses a qualitative approach with a descriptive method. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results of the study show that the management of Arabic language learning programs includes the stages of planning, implementation, and evaluation of learning programs. Planning is carried out by designing the curriculum, determining learning methods, and preparing competent teaching staff. The implementation of the program is conducted through classroom learning activities as well as supporting activities such as muhadharah (speech practice), muhadatsah (conversation practice), and the implementation of an Arabic language environment (bi’ah lughawiyah). Evaluation is conducted periodically to determine the success of the program and the development of the students’ language abilities. With proper program management, the Arabic language competence of the santri can improve significantly.